Designers' guide to EN 1994-2 : Eurocode 4, design of steel and composite structures. Part 2, - Hendy, C. R. (Designers' guides to the Eurocodes., 2006)
EN 1994-2 is one standard of the Eurocode suite & describes the principles & requirements for safety, serviceability & durability of composite steel & concrete bridges. This guide provides the user with guidance on the interpretation & use of EN 1994-2 through worked examples in relation to the general rules & the rules for bridges.